PELAYANAN ADMINISTRASI TATA USAHA DI MTS AL-IKHLAS PALEMBANG - Maryance Maryance (Pusat Riset dan Inovasi Nasional, 2022)
This article is entitled Administrative Administration Services at MTs Al-Ikhlas Palembang. The purpose of this study is to find out how the Administrative Services at MTs Al-Ikhlas. In this study using qualitative methods. The informants in this study were the head of administration, the head of the madrasa, the deputy head of the madrasa, teachers and other stakeholders. Data collection techniques through the method of observation, interviews and documentation. The data analysis technique in this researcher uses data reduction, data presentation, verification and checking the validity of the data. The results of the study indicate that Administrative Administration Services at MTs Al-Ikhlas Palembang have been running well including organizational management services and staffing which includes several jobs such as determining the right organizational structure, dividing tasks and authorities to evaluating ongoing programs, financial management services , which has carried out management functions ranging from planning needs to controlling activities, data and information management services that have been supported by good resources, archive management services and student academic services. All service activities run in accordance with applicable procedures and stakeholders in carrying out their duties in accordance with their respective main duties and functions.